2022
DOI: 10.24014/sjme.v8i2.19868
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Bibliometrik Penggunaan Geogebra dalam Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa Dekade Terakhir

Maximus Tamur,
Laurensia Lidia Jedia,
Rofina Kurniyati
et al.

Abstract: Geogebra dicirikan oleh keunggulan visualisasi dan dinamis yang menarik serta memberikan manfaat yang luas terhadap kemampuan pemecahan masalah matematis siswa (KPMM). Saat ini telah banyak penelitian tentang pengaruh Geobera terhadap KPMM siswa.  Namun belum ada yang mereview lintasan studi terkait pengaruh Geogebra terhadap KPMM siswa. Untuk mengisi kesenjangan tersebut maka penelitian ini bertujuan untuk memberikan tinjauan bibliometrik dari 75 studi tentang pengaruh Geobera terhadap KPMM siswa dari databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
2
1
0
1
Order By: Relevance
“…The research results show that the number of publications between 2010-2019 is very significant. This is in line with the results of bibliometric analysis from previous studies, which showed an increasing trend until 2019 [1], [3], [21]- [23]. Furthermore, the downward trend from 2019 to 2021 was mediated by the impact of COVID-19, as seen from the results of previous research in 2019 [21].…”
Section: Fig 3 Mapping Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…The research results show that the number of publications between 2010-2019 is very significant. This is in line with the results of bibliometric analysis from previous studies, which showed an increasing trend until 2019 [1], [3], [21]- [23]. Furthermore, the downward trend from 2019 to 2021 was mediated by the impact of COVID-19, as seen from the results of previous research in 2019 [21].…”
Section: Fig 3 Mapping Analysissupporting
confidence: 91%
“…This is in line with the results of bibliometric analysis from previous studies, which showed an increasing trend until 2019 [1], [3], [21]- [23]. Furthermore, the downward trend from 2019 to 2021 was mediated by the impact of COVID-19, as seen from the results of previous research in 2019 [21]. This makes perfect sense because, during COVID-19, little research was carried out due to social restriction policies [24], [25].…”
Section: Fig 3 Mapping Analysissupporting
confidence: 89%
“…Next, the Publish or Perish (PoP) program was used to collect data on the influence of AR use in education. The use of PoP supports transparency and quality of data search [36]- [38]…”
Section: Literature Searchmentioning
confidence: 98%
“…Bibliometrik juga dapat diartikan sebagai suatu kajian yang mengukur perkembangan penelitian, literatu, buku atau dokumen pada bidang tertentu baik secara kuantitatif maupun kualitatif dengan menggunakan metode statistika (Hakim, 2020). Analisis bibliometrik yang digunakan adalah analisis bibliometrik deskriptif yang bertujuan mengkaji atau mengevaluasi terkait suatu media pembelajaran matematika (Tamur et al, 2022). Dalam analisis bibliometrik, perekaman kata kunci co-accurrence menunjukkan kata kunci yang paling umum muncul dalam dokumen yang dianalisis (Melia Astiana, Maya Malinda, Anny Nurbasari, 2021).…”
Section: Metodeunclassified